2016
DOI: 10.1016/j.trsl.2015.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic targeting of inflammation and tryptophan metabolism in colon and gastrointestinal cancer

Abstract: Colorectal cancer (CRC) is the third most common cancer worldwide and the second leading cause of cancer death in the United States. Cytotoxic therapies cause significant side effects for most patients and do not offer cure in many advanced cases of CRC. Immunotherapies are a promising new approach to harness the body’s own immune system and inflammatory response to attack and clear the cancer. Tryptophan metabolism along the kynurenine pathway is a particularly promising target for immunotherapy. Indoleamine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
66
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(70 citation statements)
references
References 148 publications
1
66
1
Order By: Relevance
“…Several N -acetyl amino acids including N -acetylcitrulline, N -acetylarginine, N -acetyltryptophan, and N -acetylkynurenine were also reduced in men later diagnosed with prostate cancer, possibly indicating increased post-translational protein N -terminal acetylation (Aksnes et al , 2015) and aminoacetylase activity, the latter having been related to increased cell proliferation and carcinogenesis (Aksnes et al , 2015), and histone-chromatin gene regulation (Eberharter and Becker, 2002). Also inversely associated were tryptophan metabolites that influence the role of inflammation in cancer progression (Prendergast et al , 2014; Santhanam et al , 2016). Tryptophan and kynurenine pathway metabolites have been previously associated with several, particularly gastrointestinal, cancers (Uyttenhove et al , 2003; Witkiewicz et al , 2008; Liu et al , 2009; Koblish et al , 2010; Balachandran et al , 2011; Zhang et al , 2011a;, 2011b; Ferdinande et al , 2012; Zhang et al , 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Several N -acetyl amino acids including N -acetylcitrulline, N -acetylarginine, N -acetyltryptophan, and N -acetylkynurenine were also reduced in men later diagnosed with prostate cancer, possibly indicating increased post-translational protein N -terminal acetylation (Aksnes et al , 2015) and aminoacetylase activity, the latter having been related to increased cell proliferation and carcinogenesis (Aksnes et al , 2015), and histone-chromatin gene regulation (Eberharter and Becker, 2002). Also inversely associated were tryptophan metabolites that influence the role of inflammation in cancer progression (Prendergast et al , 2014; Santhanam et al , 2016). Tryptophan and kynurenine pathway metabolites have been previously associated with several, particularly gastrointestinal, cancers (Uyttenhove et al , 2003; Witkiewicz et al , 2008; Liu et al , 2009; Koblish et al , 2010; Balachandran et al , 2011; Zhang et al , 2011a;, 2011b; Ferdinande et al , 2012; Zhang et al , 2013).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the inflammatory microenvironment consists of many important components such as tumor cells, stromal cells, and immune and inflammatory cells. All of these components interact intimately and produce chemokines, growth factors, and adhesion molecules, and further promote the initiation and progression of many cancers [11,12]. …”
Section: Discussionmentioning
confidence: 99%
“…In comparison, Oh et al (41) reported 929 significant epithelial-stromal coexpression interactions among 11,700 ϫ 11,700 ϭ 136,890,000 pairwise associations tested in normal breast tissue. Interestingly, all the top detected genes have been implicated in the link between inflammation and cancer of the colon (5,18,20,35,39,44,46,49,56,62). Additional systems-level analyses on independent RNA-Seq data sets are needed to further explore how colonic stromal and epithelial interactions temporally evolve during malignant transformation.…”
Section: Discussionmentioning
confidence: 99%